Mobility in the European Aristocracy during the Age of Enlightenment: The Example of Princess Helena Potocka - Figeac, Michel (Historical Studies on Central Europe, 2024)
Helena Potocka offers a wonderful case study because she was a perfect representative of the high European aristocracy under French influence. Educated in a Parisian religious house, she had the culture of the young girls of the nobility of Versailles. Her matrimonial alliance with the son of the Prince de Ligne poses the problem of matrimonial strategies. Helena was both a free and rebellious spirit who believed in her ability to build her happiness with the side she chose. This is why she left Charles de Ligne; she thought she had discovered her soul mate with Vincent Potocki, but in reality, it must have been a lifelong quest. The Potocki couple are then torn between the financial resources of distant Ukraine, where the immense properties that finance them are located, and Parisian social life. Potocki’s very particular family situation triggered incessant mobility throughout his life, but this mobility had very varied motivations and was one of the main characteristics of the high European aristocracy, which had the financial means to travel to all parts of Europe. The international circulations of the aristocracy produced, within this social group, a growing cosmopolitanism: in fact, the aristocrats of the various nations of Europe rubbed shoulders and mixed more and more in the various spaces of sociability that were theirs. This worldly cosmopolitanism led to the progressive diffusion within this elite of common modes of consumption, behavior, and thought—in short, an aristocratic European Habitus.